Role of spin-orbit interaction in the ultrafast demagnetization of small iron clusters - SANVITO, STEFANO (My University, 2016)
The ultrafast demagnetization of small iron clusters initiated by an intense optical excitation is studied from the time-dependent spin density functional theory (TDSDFT). In particular we investigate the effect of the spin-orbit interaction on the onset of the demagnetization process. It is found that demagnetization occurs locally, in the vicinity of the atomic sites, and the initial rate of spin loss, coherent with the laser field, is proportional to the square of the ionic spin-orbit coupling strength λ . A simplified quantum spin model comprising spin-orbit interaction and a time-dependent magnetic field is found to be the minimal model able to reproduce our ab initio results. The model predicts the λ 2 dependence of the onset rate of demagnetization when it is solved either analytically for the small t regime, or numerically integrated in the time domain. Our findings are supported by additional TDSDFT simulations of clusters made of Co and Ni.
PUBLISHED
Export Date: 5 January 2017
Keywords: ultrafast demagnetization; ultrafast demagnetization